(untitled) (International journal of artificial intelligence, 2025)
This article examines the contemporary characteristics of energy diplomacy among Central Asian states, focusing on the period from 2010 to 2024. The research analyzes the evolution of regional energy cooperation, strategic partnerships, and the changing dynamics of energy politics in Central Asia. Through comprehensive literature review and analysis of diplomatic relations, the study highlights the growing importance of energy security and regional integration in shaping interstate relations.